2008
DOI: 10.1117/1.2939400
|View full text |Cite
|
Sign up to set email alerts
|

In vivo optical coherence tomography detection of differences in regional large airway smoke inhalation induced injury in a rabbit model

Abstract: Smoke inhalation injury causes acute airway injury that may result in airway compromise with significant morbidity and mortality. We investigate the ability of high resolution endobronchial optical coherence tomography (OCT) to obtain real-time images for quantitatively assessing regional differences between upper tracheal versus lower tracheal and bronchial airway injury responses to smoke inhalation in vivo using a prototype spectral domain (SLD)-OCT system we constructed, and flexible fiber optic probes. 33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…The animals (male adult New Zealand White, 4 to 4.5 kg, Western Oregon Rabbit Co. Philomath, Oregon) were anesthetized with a ketamine-xylazine mixture, intubated with a 3.5 mm endotracheal tube, and imaged with our OCT system as described above and previously. 11,15,16 All methods were approved by the Institutional Animal Care and Use Committee at the University of California, Irvine (Protocol No. 2007-2754).…”
Section: In Vivo Wall Motion Analysis Of Rabbit Tracheamentioning
confidence: 99%
See 1 more Smart Citation
“…The animals (male adult New Zealand White, 4 to 4.5 kg, Western Oregon Rabbit Co. Philomath, Oregon) were anesthetized with a ketamine-xylazine mixture, intubated with a 3.5 mm endotracheal tube, and imaged with our OCT system as described above and previously. 11,15,16 All methods were approved by the Institutional Animal Care and Use Committee at the University of California, Irvine (Protocol No. 2007-2754).…”
Section: In Vivo Wall Motion Analysis Of Rabbit Tracheamentioning
confidence: 99%
“…Endoscopic probes have been developed for many organs, allowing imaging of the blood vessels, esophagus, urethra, and airways with a resolution previously only available via biopsy and histological preparation. [14][15][16][17][18][19][20][21] Recently developed Fourier-domain OCT techniques maintain the same spatial resolution while offering video-frame rates (up to 100 frames/s). 20,21 Furthermore, unlike ultrasound, OCT can be used in noncontact modes and in air-filled lumens, such as the airways.…”
Section: Introductionmentioning
confidence: 99%
“…Increased thickening of basement membrane according to the epithelial thickening was apparent with following OCT monitoring. In several studies, the extent of injury has been quantitatively measured with this spectral-domain OCT system [13][14][15]. In this study, we first measured thickness of the basement membrane in injured tracheas.…”
Section: Discussionmentioning
confidence: 99%
“…As a nonionizing, non-invasive medical imaging modality, optical coherence tomography (OCT) has been used to perform high resolution, cross-sectional imaging of biological tissues. Previous studies [6][7][8][9][10][11] have demonstrated the flexibility of OCT to image the airways of different animals in vivo. Among them, the Fourier domain long-range swept source OCT (LR-SSOCT) exhibits higher sensitivity, faster imaging speed and an extended imaging range compared to conventional OCT systems.…”
Section: Introductionmentioning
confidence: 99%